Caracterización de la regla de colisión de Huygens-Newton mediante una cantidad vectorial invariante Galileo - Díaz-Solórzano, S.; González-Díaz, L.A. (Revista Mexicana de Física E, 2012)
We restate the collision rule Huygens - Newton in terms of a vector quantity we call the collision vector $\vec{A}(ε)$. The collision vector is invariant and covariant Galileo. It contains information about the process of interaction and scattering of the particles. The geometric and energetic sense of the collision rule Huygens-Newton in terms of the collision vector is shown.